2012
DOI: 10.2174/1874155x01206010026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimization of the Double-Axle Steering Mechanism with Dynamic Loads

Abstract: A hierarchical optimization procedure for the optimal synthesis of a double-axle steering mechanism used in truck with dynamic loads is presented. A multibody model of double-axle steering mechanism is presented to characterize the leaf spring effect. The influences of dynamic loads, the motion interference of steering linkage resulted from the elastic deformation of leaf spring, and the effects of wheel slip angles and the position discrepancies of wheel speed rotation centers are studied systematically. A hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…When the driver acts on the steering wheel, the wheels will turn at corresponding angles to make the vehicle turn. With 2 axles steer on the front, the steer wheels are linked via levers to ensure correct kinematics when turning [12,13,32]. The wheels on a steering axle still ensure alignment and are described by the Ackermann formula with the steering wheel rotation angle δSW being the input rule according to the following formulas:…”
Section: Model Of 2-axle Steering Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…When the driver acts on the steering wheel, the wheels will turn at corresponding angles to make the vehicle turn. With 2 axles steer on the front, the steer wheels are linked via levers to ensure correct kinematics when turning [12,13,32]. The wheels on a steering axle still ensure alignment and are described by the Ackermann formula with the steering wheel rotation angle δSW being the input rule according to the following formulas:…”
Section: Model Of 2-axle Steering Systemmentioning
confidence: 99%
“…Rollover, on the other hand, is caused by a large inertial force that creates a moment strong enough to be a greater anti-rollover moment, causing the vehicle to rollover. This state can occur during turning maneuvers on roads with high adhesion coefficients, or even when colliding with other objects on roads with low adhesion coefficients [6,7,8,9].The structure of multiple steering axles and the kinematic alignment of the steering axle ensure the vehicle is more stable when turning [10,11,12,13]. The 'Walking Beam' suspension structure will help distribute the load and increase traction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical optimization of steering linkage was done by dividing the system into number of sub-system objective functions. Results revealed that hierarchical optimization procedure is more effective and robust as compared to the simultaneously optimized system [4]. Researcher also studied dynamic simulation of steering mechanism by varying force with respect to time [5].…”
Section: Introductionmentioning
confidence: 99%
“…3.3. This kind of multi-axle vehicle can only have one non-steerable axle to guarantee steerability without slipping, and all the wheels are required to share the same center of rotation at any moment as stated in [91] and [92]. The three-axle vehicle of width w v in Fig.…”
Section: Multi-axle Vehiclementioning
confidence: 99%